Development of halal ontology - Che Daud, Suriana; Mustafa, A'dillah; Baharuddin, Kasmarini (Universiti Teknologi MARA, Kedah, 2019)
Ontology plays a significant role in helping Islamic scholars and entrepreneur in understanding, organizing the diversity branch of knowledge in the halal industry. In a recent development on halal research, massive diversity of knowledge production on halal issues including halal industry, certification, and legislation. The halal industry is amongst the growing subject in Islamic knowledge. Ontology is view as an effective tool in organizing, and access and retrieval of information in information management practice. Librarians play a vital role in facilitating access to information by introducing a dedicated and structured access tool. The growth of interest in Islamic knowledge motivates librarians and Islamic scholars in initiating a specialized ontology in Islamic knowledge. The objectives of the paper are to identify halal subject entries and to develop Standard Subject focusing on halal industry. Ontology development is a meticulous process of identifying and classifying subject entries. The extraction process is to confirm the ontology development represent the hierarchical classification of Islamic knowledge, at the same time facilitates access to the halal industry. Hence, it serves as a vital reference for the halal researcher, Islamic scholar, academicians, and Islamic entrepreneur. The first Islamic ontology focusing on Halal Industry specifically will benefit Islamic scholars and entrepreneur in providing solution and understanding to the halal industry. This process establishes the Subject Guidelines on Halal Industry which is in highly demanding in the current Islamic knowledge development scenario.